NOT SUFFERING FOOLS GLADLY: CRAFTING PROSOCIAL COMMUNITY IN ONLINE MULTIPLAYER MINECRAFT - Woodbridge, Kenzie Ann Burniston (AoIR Selected Papers of Internet Research, 2018)
Over 700 million people worldwide are socializing and spending time, sometimes significant amounts, in online multiplayer games, and these social spaces can be important sites of community. Unfortunately, levels of civility, aggression, and mutual helping can vary significantly between game spaces. Given their ubiquity and importance in so many people’s lives, it is critical to understand how a prosocial community can be created and maintained over time in these spaces for those who want them. This research uses virtual ethnography and interpretive phenomenological analysis to examine how moderation and community development strategies, game design elements, and player behaviours are experienced and can be influenced by players in prosocially-oriented online multiplayer Minecraft servers. It is clear that it is the prosocial orientation of players and the commitment, social skill, and integrity of server moderators that is most key to creating and maintaining a prosocial gaming environment and that although game design can support prosociality, game design factors appear to be much less important overall. Attracting the right players—and refusing entry to the wrong ones—is the most important concern.